1998
DOI: 10.1159/000025601
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Plasminogen Activator Colocalizes with CD25+ Cells in Atherosclerotic Vessels

Abstract: Proteolytic activity in vascular tissue is necessary for cellular migration, remodelling of extracellular matrix and the development of atherosclerotic lesions. Inflammatory cells, mainly macrophages, are numerous in atherosclerotic plaques and may synthesize and secrete proteolytic enzymes. The principal activator of plasminogen in tissues is urokinase plasminogen activator (u-PA). To determine if an activated phenotype of inflammatory cells colocalizes with local expression of u-PA in atherosclerotic vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…uPA is highly expressed in macrophage-rich areas adjacent to the shoulder regions of advanced human atherosclerotic lesions 16, 17, 38. “Culprit” human carotid plaques have increased expression of plasminogen activators and elevated plasmin activity compared to uncomplicated plaques,39 and both elevated plasminogen activator mRNA and increased uPA receptor expression by macrophages correlate with intraplaque hemorrhage and rupture in acutely symptomatic human carotid plaques 40, 41.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uPA is highly expressed in macrophage-rich areas adjacent to the shoulder regions of advanced human atherosclerotic lesions 16, 17, 38. “Culprit” human carotid plaques have increased expression of plasminogen activators and elevated plasmin activity compared to uncomplicated plaques,39 and both elevated plasminogen activator mRNA and increased uPA receptor expression by macrophages correlate with intraplaque hemorrhage and rupture in acutely symptomatic human carotid plaques 40, 41.…”
Section: Discussionmentioning
confidence: 99%
“…Some MMPs are activated within the secretion pathway by proprotein convertase; however, for most MMPs, including essentially all MMPs implicated in plaque rupture, the activation mechanism is unknown 15. Plasmin, an abundant serine proteinase that could be activated within the plaque by macrophage-expressed urokinase plasminogen activator (uPA),16, 17 is often considered to be a critical activator of MMPs in the vessel wall 18, 19…”
mentioning
confidence: 99%
“…Other studies have reported additional links between the above molecules, e.g. colocalization of neutrophil elastase, uPA, and uPAR (72) or colocalization of uPA and IL-2sR␣ (73). Finally pathogens are known to interact in a specific manner with components of fibrinolytic pathways as well as with CRP (74).…”
Section: Differentiation Of Etiologic Agent Class By Examination Of Hmentioning
confidence: 98%
“…2A) The presence of inflammatory cells in diseased blood vessels does not imply that these cells are necessarily activated. There is evidence that there are subpopulations of activated and non-activated macrophages [29,59] and T cells [60] within plaques. Within the vascular wall, activated immune cells influence blood flow through the release of cell mediators.…”
Section: Chemokine Attraction Of Leukocytes (Fig 1b)mentioning
confidence: 99%